Kajian Bibliometrika Menggunakan Analisis Sitiran terhadap Skripsi Program Studi Pendidikan Bahasa dan Sastra Indonesia FBS UNP Tahun 2005-2009 - Elva Rahmah (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2011)
The purposes of this study are: (1) to know the ratings of the most cited authors, (2) to determine what means of bibliography was cited most frequently, (3) to know what subject is often cited and, (4) to know the obsolescence of the cited literature in the undergraduate theses written by students of Indonesian Language and Literature Education Study Program. The research method used a quantitative approach through bibliometric analysis to determine the characteristics of the papers with citation analysis. The results are (1) the author that is most widely cited is M. Atar Semi, and the top 5 authors that are widely cited are M. Atar Semi, Gorys Keraf, Hendry Guntur Tarigan, Suharsimi Arikunto, and Abdurahman; (2) book (80.24%) is a type of literatures that are most widely cited in the theses; (3) the most favorite subject of the theses is "effective sentences"and, (4) the publication time of literature cited in the theses is 21.4 years. Keywords: bibliometric, citation analysis, literature obsolescence